Managerial performance evaluation and organizational form - Michael Krapp; Wolfgang Schultze; Andreas Weiler (Contemporary Accounting Research, 2023)
We study the relative efficiency of centralized versus decentralized organizational forms given optimized managerial performance evaluation within an incomplete contracting framework with risk-averse agents under moral hazard. Decentralization and performance evaluation are complementary control choices and the efficiency of an organizational form depends on the design of performance evaluation. Divisions can make relationship-specific investments that not only improve firm performance, but also increase compensation risk. We find that pure divisional performance evaluation is optimal under centralization, whereas under decentralization, optimal compensation contracts include a combination of divisional and firm-wide performance evaluation. When comparing both organizational forms, we find that the optimal form depends on managers' degree of risk-aversion and the uncertainty of the business environment. Contrary to previous literature, we find that centralization dominates in many situations, particularly at high degrees of risk-aversion and high uncertainty.
Keywords: 650; budgeting; hold-up; performance evaluation; transfer pricing; budgétisation; établissement de prix de transfert; évaluation de la performance; problème de renonciation